The Role of WNT5a and TGF‐β1 in Airway Remodelling and Severe Asthma - Daud, Tariq; Roberts, Sheree; Zounemat Kermani, Nazanin; Richardson, Matthew; Heaney, Liam G.; Adcock, Ian M.; Amrani, Yassine; Bradding, Peter; Siddiqui, Salman (Allergy (Copenhagen), 2025)
ABSTRACT Background Airway remodelling is a feature of severe asthma with airway epithelial damage observed frequently. We evaluated the role of WNT5a and TGF‐β1 in asthmatic airway biopsies and in sputum and bronchial brushings assessed their role in remodelling. Methods WNT5a and TGF‐β1 protein expression were assessed in the lamina propria epithelium of people with asthma (GINA 1–3, n‐8 and GINA 4–5, n‐14) and healthy subjects (n‐9), alongside relevant remodelling markers. The effects of WNT5a and TGF‐β1 on BEAS‐2B epithelial cell wound healing and differentiation were assessed in vitro. Replication was performed in the Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes (U‐BIOPRED) study in sputum (n = 120) and bronchial brushes (n = 147). Results WNT5a and TGF‐β1 protein expression were significantly increased in the airway epithelium and lamina propria in asthma patients with concurrent airflow limitation or severe disease. Furthermore, WNT5a protein expression in the lamina propria correlated with tissue eosinophils and vascular remodelling. Airway epithelial WNT5a was co‐localised predominantly to airway basal cells and correlated with Th17 gene expression (r = 0.40, p = 0.025) and both the % intact (rs = 0.54, p = 0.001) and % denuded epithelium (rs = −0.39, p = 0.003). Experiments in BEAS‐2B cells confirmed that WNT5a at maximal physiological concentrations (1 μg/mL), promoted epithelial wound healing, independently of TGF‐β1, as well as induction of EMT‐like morphology. WNT5a mRNA was associated with severe asthma, airflow limitation, sputum eosinophilia and Th2, and Th17 and neutrophil activation transcriptomes in sputum in U‐BIOPRED. Conclusion WNT5a is associated with both airway remodelling and severe asthma. Trial Registration ClinicalTrials.gov identifier: NCT01982162 This study evaluates the role of WNT5a and TGF‐β 1 in severe asthma and airway remodelling. When compared to healthy, both TGF‐β1 and WNT5a are significantly increased in the airway in patients with asthma irrespective of airflow limitation. WNT5a correlates with the epithelial barrier integrity and promotes wound healing. BEAS‐2B, human bronchial epithelial cell line; FEV1, forced expiratory volume in 1 s; FVC, forced vital capacity; RT‐PCR, real time polymerase chain reaction; TGF‐β1, transforming growth factor beta 1; U‐BIOPRED, Unbiased Biomarkers Respiratory DiseaseOutcomes, Prediction cohort; WNT5a, wingless‐type MMTV integration site family member 5a.